Antimicrobial, Antioxidant and Cytotoxic Activities of Glochidion multiloculare (Roxb. ex Willd.) Müll. Arg. (Euphorbiaceae) (Dhaka University Journal of Pharmaceutical Sciences, 2013)
The methanol extract (ME) of the powdered bark of Glochidion multiloculare and its six vacuum liquid chromatographic (VLC) fractions (Fa-f) were investigated for antimicrobial, cytotoxic and antioxidant activities. Only fractions Fc and Fd showed mild antimicrobial activity. Significant free radical (DPPH) scavenging activity was found in Ff (IC50 value = 9.27±0.117 ?g/ml). The total phenolic content was measured involving Folin-Ciocalteu reagent and it was the highest in fraction Fe (187.00±1.74 mg of GAE/gm of sample). Cytotoxicity (LC50) by brine shrimp lethality bioassay was found to be significant for Fb (0.023±0.001 ?g/ml), Fc (0.3±0.01 ?g/ml) and Fd (0.117±0.0015 ?g/ml). DOI: http://dx.doi.org/10.3329/dujps.v11i2.14560 Dhaka Univ. J. Pharm. Sci. 11(2): 117-120, 2012 (December)